Progress Toward Development of Effective and Safe African Swine Fever Virus Vaccines - Sang, Huldah; Miller, Gabrielle; Lokhandwala, Shehnaz; Sangewar, Neha; Waghela, Suryakant D.; Bishop, Richard P.; Mwangi, Waithaka (Frontiers in Veterinary Science, 2020)
African swine fever is a major concern due to its negative impact on pork production in affected regions. Due to lack of treatment and a safe vaccine, it has been extremely difficult to control this devastating disease. The mechanisms of virus entry, replication within the host cells, immune evasion mechanisms, correlates of protection, and antigens that are effective at inducing host immune response, are now gradually being identified. This information is required for rational design of novel disease control strategies. Pigs which recover from infection with less virulent ASFV isolates can be protected from challenge with related virulent isolates. This strongly indicates that an effective vaccine against ASFV could be developed. Nonetheless, it is clear that effective immunity depends on both antibody and cellular immune responses. This review paper summarizes the key studies that have evaluated three major approaches for development of African Swine Fever virus vaccines. Recent immunization strategies have involved development and in vivo evaluation of live attenuated virus, and recombinant protein- and DNA-based and virus-vectored subunit vaccine candidates. The limitations of challenge models for evaluating ASFV vaccine candidates are also discussed.